The Role of Fiscal Decentralization and Human Resource Quality in The Welfare Of Underdeveloped Regions in Indonesia: The Role of Fiscal Decentralization and Human Resource Quality in The Welfare Of Underdeveloped Regions in Indonesia - Fadhlurrahman Ruslan; Nurhayati (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
This study aims to see the advantage of fiscal decentralization and human development on welfare in 62 underdeveloped districts in Indonesia. The data used is secondary data of 62 underdeveloped districts in Indonesia in 2016-2020 period for panel data regression. The result showed that fiscal decentralization, namely DAU, and life expectation number with 5% error rate are statistically significant have sign in accordance with expectation, then H1a and H2a are accepted. While fiscal decentralization, namely DAK and DBH, with average time of school has no influence on the welfare of underdeveloped regions in Indonesia